Lobbying at the local level: social assets in Russian firms - Tuuli Juurikkala; Olga Lazareva (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
In the planned economy firms were made responsible for providing their workers with social services, such as housing, day care and medical care.In the transforming Russia of the 1990s, social assets were to be transferred from industrial enterprises to the public sector.The law on divestment provided little more than general principles.Thus, for a period of several years, property rights concerning a major part of social assets, most notably housing, were not properly defined, as transfer decisions were largely left to the local level players.Strikingly, the time when assets were divested varied considerably across firms.In this paper we utilize recent survey data from 404 medium and large industrial enterprises in 40 Russian regions and apply survival data analysis to explore the determinants of divestiture timing. Our results show that in municipalities with higher shares of own revenues in their budget and thus weaker fiscal incentives, firms used their social assets as leverage to extract budget assistance and other forms of preferential treatment from local authorities. We also find evidence that less competitive firms were using social assets to cushion themselves from product market competition.At the same time, we do not find any role for local labor market conditions in the divestment process.
URN:NBN:fi:bof-201408072102
Keywords: 330